2009
DOI: 10.4103/0970-9371.54870
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytology of Kikuchi Fujimoto disease

Abstract: Kikuchi disease (KD) is an enigmatous, self-limiting, rarely fatal, disease of young females. The self-limiting disorder usually occurs in Asian women in their late 20s or early 30s. Typically it runs a benign course and appears to resolve spontaneously one to six months after definitive diagnosis. We report a 27 years old lady presenting with cervical lymphadenopathy. Fine needle aspiration cytology of the node clinched the diagnosis revealing crescentic histiocytes, plasmacytoid monocytes, extracellular (kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, Hasan et al . reported that, with clear symptoms and characteristic features of KFD in FNAC results, the diagnosis of KFD may be established without lymphadenectomy [ 12 ]. Yu et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Hasan et al . reported that, with clear symptoms and characteristic features of KFD in FNAC results, the diagnosis of KFD may be established without lymphadenectomy [ 12 ]. Yu et al .…”
Section: Discussionmentioning
confidence: 99%